PERBANDINGAN DEIKSIS PADA DUA BUKU AJAR: ANALISIS KONTRASTIF BIPA DAN BAHASA INGGRIS - Destiani, Destiani; Andayani, Andayani; Rohmadi, Muhammad (Universitas Pendidikan Indonesia, 2018)
Indonesian language is a foreign language at Sebelas Maret University for students from abroad. Foreign students who communicate with English encounter difficulty to understand and use deixis. This study tried to contrast deixis on two textbooks, Bahasa Indonesia bagi Penutur Asing (BIPA)/Indonesian for foreigner and English textbook. The study was conducted through qualitative study with contrastive analysis. AntConc version 3.4.5 was used to identify deixis corpus from BIPA textbook. The concordance from the BIPA textbook was compared with sentences on the English textbook. The analysis found that deixis from those textbooks were different in term of position, form and use. Indonesian deixis can either precede or follow a noun or verb while English deixis appeared only before a noun or verb. When coming together with plural noun, English deixis changes in the form, meanwhile Indonesian’s is not. Based on this study, BIPA teachers are suggested to bring concrete samples during teaching deixis.